Impact of Cancer History on Outcomes Among Hospitalized Patients with COVID-19. (12th May 2021) - Klein, Isaac A.; Rosenberg, Shoshana M.; Reynolds, Kerry L.; Zubiri, Leyre; Rosovsky, Rachel; Piper-Vallillo, Andrew J.; Gao, Xin; Boland, Genevieve; Bardia, Aditya; Gaither, Rachel; Freeman, Hannah; Kirkner, Gregory J.; et al.
Abstract : Background: Early reports suggested increased mortality from COVID-19 in patients with cancer but lacked rigorous comparisons to patients without cancer. We investigated whether a current cancer diagnosis or cancer history is an independent risk factor for death in hospitalized patients with COVID-19. Patients and Methods: We identified patients with a history of cancer admitted to two large hospitals between March 13, 2020, and May 10, 2020, with laboratory-confirmed COVID-19 and matched them 1:2 to patients without a history of cancer. Results: Men made up 56.2% of the population, with a median age of 69 years (range, 30–96). The median time since cancer diagnosis was 35.6 months (range, 0.39–435); 80% had a solid tumor, and 20% had a hematologic malignancy. Among patients with cancer, 27.8% died or entered hospice versus 25.6% among patients without cancer. In multivariable analyses, the odds of death/hospice were similar (odds ratio [OR], 1.09; 95% confidence interval [CI], 0.65–1.82). The odds of intubation (OR, 0.46; 95% CI, 0.28–0.78), shock (OR, 0.54; 95% CI, 0.32–0.91), and intensive care unit admission (OR, 0.51; 95% CI, 0.32–0.81) were lower for patients with a history of cancer versus controls. Patients with active cancer or who had received cancer-directed therapy in the past 6 months had similar odds of death/hospice compared with cancer survivors (univariable OR, 1.31; 95% CI, 0.66–2.60; multivariable OR, 1.47; 95% CI, 0.69–3.16). Conclusion: Patients with a history of cancer hospitalized for COVID-19 had similar mortality to matched hospitalized patients with COVID-19 without cancer, and a lower risk of complications. In this population, patients with active cancer or recent cancer treatment had a similar risk for adverse outcomes compared with survivors of cancer. Implications for Practice: This study investigated whether a current cancer diagnosis or cancer history is an independent risk factor for death or hospice admission in hospitalized patients with COVID-19. Active cancer, systemic cancer therapy, and a cancer history are not independent risk factors for death from COVID-19 among hospitalized patients, and hospitalized patients without cancer are more likely to have severe COVID-19. These findings provide reassurance to survivors of cancer and patients with cancer as to their relative risk of severe COVID-19, may encourage oncologists to provide standard anticancer therapy in patients at risk of COVID-19, and guide triage in future waves of infection. Abstract : This article focuses on whether a current cancer diagnosis or cancer history is an independent risk factor for death or hospice admission in hospitalized patients with COVID-19.